Teacher's Verbal Feedback in the Classroom Interaction - Agus - Rahmat; Umar Mukhtar Munir (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2018)
This research aims to find out: (1) verbal feedback used by EFL teachers in classroom interaction, (2) function of verbal feedback used by EFL teachers in classroom interaction. This research employs descriptive qualitative research. The participants of this research were English teachers and the students of SMA Buq’atun Mubarakah. The data of this research were collected by recording the classroom interaction. The obtained data was analyzed by using Miles & Huberman analysis. The results of this research reveal that (1) the verbal feedback used by EFL teachers in classroom interaction, are (a) questioning, (b) praising (c) clarifying (d) comment (e) repeating (f) explicit correction and (g) Treating. (2) The functions of verbal feedback used by the teacher are a) interactional feedback, and (b) evaluative feedback.